Case-control study of leukaemia and non-Hodgkin's lymphoma among children aged 0-4 years living in west Berkshire and north Hampshire health districts. Issue 6878 (6th March 1993) - Roman, E; Watson, A; Beral, V; Buckle, S; Bull, D; Baker, K; Ryder, H; Barton, C
Abstract : OBJECTIVE–To investigate the relation between parental employment in the nuclear industry and childhood leukaemia and non-Hodgkin's lymphoma. DESIGN–Case-control study. SETTING-West Berkshire and Basingstoke and North Hampshire District Health Authorities. SUBJECTS–54 children aged 0-4 years who had leukaemia or non-Hodgkin's lymphoma diagnosed during 1972-89, who were born in the study area and were resident there when cancer was diagnosed. Six controls were selected for each case: four from hospital delivery registers and two from livebirth registers maintained by the NHS central register. Controls were matched for sex, date of birth (within six months), and area of residence at birth and time of diagnosis. MAIN OUTCOME MEASURES–Parents' employment by the nuclear industry and exposure to ionising radiation at work. RESULTS–Five (9%) of the 54 cases and 14 (4%) of the 324 controls had fathers or mothers, or both, who had been employed by the nuclear industry (relative risk 2.2, 95% confidence interval 0.6 to 6.9). Nuclear industry employees who work in areas where exposure to radiation is possible are given film badges to monitor their exposure to external penetrating ionising radiation. Three fathers of cases and two fathers of controls (and no mothers of either) had been monitored in this way before their child was conceived (relative risk 9.0, 95% confidence interval 1.0 to 107.8). No father (of a case or control) had accumulated a recorded dose of more than 5 mSv before his child was conceived, and no father had been monitored at any time in the four years before his child was conceived. A dose-response relation was not evident among fathers who had been monitored. CONCLUSIONS–These results suggest that the children of fathers who had been monitored for exposure to external penetrating ionising radiation in the nuclear industry may be at increased risk of developing leukaemia before their fifth birthday. The finding is based on small numbers and could be due to chance. If the relationship is real the mechanisms are far from clear, except that the effect is unlikely to be due to external radiation; the possibility that it could be due to internal contamination by radioactive substances or some other exposure at work should be pursued. The above average rates of leukaemia in the study area cannot be accounted for by these findings.